A framework for adaptive control of multi-reservoir systems under changing environment. (20th September 2021) - Zhang, Yu; Yu, Lei; Wu, Shiqiang; Wu, Xiufeng; Dai, Jiangyu; Xue, Wanyun; Yang, Qianqian
Abstract: The changing environment has led to significant changes in the supply and demand of runoff, directly affecting the benefits of the multi-reservoir systems. Adaptive operation and quantitative control can hedge against the negative effects of changing environment for multi-reservoir systems, while studies related to the general theory and methods or models of such operations are inadequate. In this context, an adaptive control framework for multi-reservoir systems is proposed from a supply and demand perspective. Under this framework, a multi-objective optimal operation model is first established for adaptive control analysis, and the adaptive control measures based on supply-side, demand-side, and supply-demand linkage perspectives are designed. The effects of different control measures are further evaluated through scenario simulation analysis to recommend control schemes, using a multi-reservoir system in the Upper Yangtze River Basin of China as an example. The results suggest that the supply-demand linkage is an effective method to minimize the negative effects of changing environment on multi-reservoir systems, such as changes in runoff, increasing demands in water supply, population growth and socioeconomic development, etc. The proposed framework is shown to be feasible and effective in developing control measures for multi-reservoir systems to adapt to changing environments, which can provide a theoretical basis for the management of multi-reservoir systems under changing environments. Highlights: A framework for adaptive control of multi-reservoir systems is developed. An optimal operation model is established for adaptive control analysis. Adaptive control measures are designed under the framework. The effects of control measures are evaluated through scenario simulation analysis. A case study is conducted based on the proposed framework using real-world data.